User Interface Aplikasi Datangin Customer Berbasis Mobile Dengan Metode Design Thinking - Meida Cahyo Untoro; Mahdia Nisrina Maharani M (Journal of Innovation Information Technology and Application (JINITA), 2022)
The development of technology today has greatly helped and facilitated human work. Almost everything can be associated with internet technology, especially in terms of business, such as on-demand services and marketplaces. PT. Come Solusi Bersama is a technology start-up company engaged in this business. So to simplify and expand the reach of its business, a mobile-based application is needed. With the Datangin Customer application, it will be easier for customers to order services/services that exist on Datangin. In making this mobile-based Datangin Customer application, of course, you have to go through the design stage. Both in terms of system and appearance design. Design thinking is especially useful when dealing with unclear or unknown problems, reframing problems in a human-centered way, brainstorming, using a hands-on approach to prototyping and testing, and trying different concepts and ideas. In this study, the author uses the Design Thinking method and tools in the form of Figma in solving existing problems. It is easier for customers to access the services available on Datangin, unlike before this application, and the interface is user-friendly, attractive, and interactive. Usability testing that the designed user interface can be accepted with a value of 83.33%